Bilateral pallidal stimulation for X-linked dystonia parkinsonism - Wadia, Pettarusp M.; Lim, Shen-Yang; Lozano, Andres M.; Adams, John R.; Poon, Yu-Yan; Diaz, Cristina Torres; Moro, Elena (American Medical Association, 2010)
Objective: To report the clinical benefits of bilateral deep brain stimulation (DBS) of the globus pallidus internus (GPi) in a patient with X-linked dystonia parkinsonism (XDP). Design: Case report. Setting: Tertiary referral center. Patient: A 40-year-old Filipino man with genetically confirmed XDP and severely disabling generalized dystonia. Intervention: Bilateral GPi DBS. Main Outcome Measures: The primary outcome measures were the Burke-Fahn-Marsden Dystonia Scale (BFMDS) severity and disability scores, and the secondary outcome measure was the Unified Parkinson Disease Rating Scores. Results: At the 1-year postoperative follow-up, there was 80.4% improvement in the BFMDS severity score and 66.7% improvement in the BFMDS disability score. Conclusion: Bilateral GPi DBS seems to be very effective in improving dystonia in XDP.